Analysis of trauma narratives reported by abused individuals - Sánchez Antillón, Antonio (2019)
The subject of the research is the traumatic ordeal caused by moral and sexual abuse during childhood, and its long-term consequences. Life stories of four adult individuals (one man and three women) between 36 and 60 years old were analyzed. The research is qualitative and the method of analysis is based on the Narrative Identity Theory. The stories have some coincident points: moral or sexual abuse; escape from their family nucleus; repetitive abuse, and current affliction due to relived experience. In the specific case of women, there are reports of suicide ideation and attempts. . It is concluded that the trauma and the rejection are consistent with the construction of an “existential no-place”.